2018
DOI: 10.15537/smj.2018.2.21038
|View full text |Cite
|
Sign up to set email alerts
|

Natural products in endodontics

Abstract: Herbal remedies are used throughout the world, either in earlier or in recent times. The number of studies on this alternative therapeutic system increased in the last decades. In this paper, the relevant literature on the use of natural products in root canal therapy is revised from a MEDLINE database search. The uses of medicinal plants in endodontics include cleaning and disinfection of root canals, intracanal medicaments between appointments, sealer cements, and for removal of obturation material. Other st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…This odor is a result from the reaction of NaOCl with water [34]. Because of safety concerns, cytotoxic reactions and the potential side effects of the synthetic irrigants, the use of herbal agents has been increased recently; studies reported that the herbal agents have an excellent biocompatibility, anti-inflammatory, antioxidant properties and increased antimicrobial activity [31,[34][35][36][37]. The most effective method to combat E. faecalis is to use 2% chlorhexidine in combination with sodium hypochlorite as endodontic irrigant, which is most often recommended [8].…”
Section: Discussionmentioning
confidence: 99%
“…This odor is a result from the reaction of NaOCl with water [34]. Because of safety concerns, cytotoxic reactions and the potential side effects of the synthetic irrigants, the use of herbal agents has been increased recently; studies reported that the herbal agents have an excellent biocompatibility, anti-inflammatory, antioxidant properties and increased antimicrobial activity [31,[34][35][36][37]. The most effective method to combat E. faecalis is to use 2% chlorhexidine in combination with sodium hypochlorite as endodontic irrigant, which is most often recommended [8].…”
Section: Discussionmentioning
confidence: 99%
“…133 Conventional antimicrobial agents include calcium hydroxide, phenolic and non-phenolic compounds, biocides, iodine, antibiotics, and natural products. 40,[134][135][136] Overall, calcium hydroxide has been the intracanal dressing most used, 137,138 however, calcium hydroxide may not be effective against all types of bacteria, since some studies have demonstrated that microorganisms like Enterococcus faecalis, Actinomyces radicidentis, and Candida albicans may become tolerant to increased pH produced by calcium hydroxide and result in treatment failure. [139][140][141] Two other antimicrobials, chlorhexidine (noted for its sustained activity) 142 and sodium hypochlorite dramatically reduce tooth mechanical properties.…”
Section: Dental Restorative Materials Modification With Ampsmentioning
confidence: 99%
“…These materials are perceived as having eminent antimicrobial effectiveness and biocompatibility. 14 15 One of these materials is propolis. It is a resinous natural byproduct, obtained from various components of the plants by the honey bees ( Apis mellifera L.).…”
Section: Introductionmentioning
confidence: 99%